2006
DOI: 10.1007/s00210-006-0090-1
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic acid decreases expression of bcl-2 and cyclin D1, inhibits proliferation, migration and induces apoptosis in cancer cells

Abstract: Betulinic acid (BA) is a pentacyclic triterpene found in many plant species, among others in the bark of white birch Betula alba. BA was reported to display a wide range of biological effects, including antiviral, antiparasitic, antibacterial and anti-inflammatory activities, and in particular to inhibit growth of cancer cells. The aim of the study was further in vitro characterization of BA anticancer activity. In this study, we demonstrated a remarkable antiproliferative effect of BA in all tested tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
94
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 19 publications
9
94
1
1
Order By: Relevance
“…Similarly, we found that caspase 3 cleavage had a role in the progression of the BA-induced apoptosis in multiple myeloma KM3 cells. The treatment of KM3 cells with various concentrations of BA (10,15, and 20 μg/mL) resulted in apoptosis rates of 15.60%±1.58%, 23.86%±2.06%, and 44.12%±3.22%, respectively, that were significantly higher than that of the control group (Figure 2). BA also contributed to caspase 3 activation in a dose-dependent manner, followed by the cleavage of PARP (Figure 4), a factor that is considered one of the major cleavage targets of caspase 3 and is involved in DNA repair in response to extracellular stress [28] .…”
Section: Wwwchinapharcom Yang L J Et Almentioning
confidence: 93%
See 2 more Smart Citations
“…Similarly, we found that caspase 3 cleavage had a role in the progression of the BA-induced apoptosis in multiple myeloma KM3 cells. The treatment of KM3 cells with various concentrations of BA (10,15, and 20 μg/mL) resulted in apoptosis rates of 15.60%±1.58%, 23.86%±2.06%, and 44.12%±3.22%, respectively, that were significantly higher than that of the control group (Figure 2). BA also contributed to caspase 3 activation in a dose-dependent manner, followed by the cleavage of PARP (Figure 4), a factor that is considered one of the major cleavage targets of caspase 3 and is involved in DNA repair in response to extracellular stress [28] .…”
Section: Wwwchinapharcom Yang L J Et Almentioning
confidence: 93%
“…Briefly, KM3 cells were maintained in RPMI-8226 medium until the mid-log phase. The cells were then seeded in 96-well plates with or without BA at various concentrations (5,10,15,20, and 25 μg/mL) at a density of 2×10 4 cells per well. After incubation for a set period of time, 20 μL MTT (5 mg/mL) was added, and the cells were incubated for another 3 h at 37 °C.…”
Section: Mtt Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The Cytotoxicity of EAF against MCF-7 cells might be related to Betulinic acid and Betulin [12,13]. The other fractions did not show significant activity against MCF-7 cells, so did the fractions of Polygonatum odoratum and Panax japonicus.…”
Section: Evaluation Of Cytotoxicitymentioning
confidence: 92%
“…Saponins have been long known as antineoplastic and immunostimulant agents. The discovery of the potent broadspectrum anticancer properties of betulinic acid however have further focused research interest on this class of plant secondary metabolites as possible anticancer lead compounds (1,3,4,7,8,15,16,32,34 A purifi ed mixture containing mostly saponins (PMS) from Astragalus corniculatus Bieb. was used in an in vivo tumor model to demonstrate its protective effect against myeloid Graffi tumour in hamsters, in collaboration with Dr. Reneta Toshkova (BAS).…”
Section: Exploitation Of the Bulgarian Flora's Biodiversity As A Sourmentioning
confidence: 99%